2015
DOI: 10.1080/15389588.2015.1030501
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Road Traffic Injuries Treated in a Large Romanian Emergency Department in Tîrgu-Mureş Between 2009 and 2010

Abstract: Objective Road traffic injuries are one of the leading causes of preventable unintentional injury. The European Injury Database estimated that in European Union (EU)-27 countries, road traffic injuries account for 10% of all injuries treated in the emergency department or admitted to the hospital, accounting for 4.2 million victims each year. We examined the characteristics and outcomes of road traffic injuries treated in a large emergency department in Romania by different types of road users. Methods Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
5
7
0
Order By: Relevance
“…Also, the male: female ratio in our study was 3.42. While this is consistent with Khorshidi’s findings, other studies in the USA, and Nigeria showed male to female ratio less than our study( 15 , 16 ). The relatively higher ratio of RTIs among young male adults can be explained by differences in attitude, social status, education, occupation, daily household activities, recreation and other cultural factors.…”
Section: Discussionsupporting
confidence: 93%
“…Also, the male: female ratio in our study was 3.42. While this is consistent with Khorshidi’s findings, other studies in the USA, and Nigeria showed male to female ratio less than our study( 15 , 16 ). The relatively higher ratio of RTIs among young male adults can be explained by differences in attitude, social status, education, occupation, daily household activities, recreation and other cultural factors.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with similar studies in other regions [24, 25]. Nevertheless, the proportion of multiple injuries was higher among vehicle occupants, bicyclists, and motorcyclists than pedestrians.…”
Section: Discussionsupporting
confidence: 93%
“…In a similar study in Australia, the opposite was found, with student involvement in crashes being rare (Mitchell, Bambach, Foster, & Curtis, 2015 Our results indicate that concussion was more common among pedestrians, bicyclists, and motorcyclists than vehicle occupants. This is consistent with similar studies in other regions (Ma et al, 2015;Majdan et al, 2015). Nevertheless, the proportion of multiple injuries was higher among vehicle occupants, bicyclists, and motorcyclists than pedestrians.…”
Section: Discussionsupporting
confidence: 93%